التسويق المباشر واثره في السلوك الشرائي: دراسة تحليلية لآراء عينة من وكلاء السلع الاستهلاكية المعمرة ومستهلكيها في مدينة الموصل - د.نجلة يونس محمد; ولاء جمال الدين نوري (PROSPECTIVE RESEARCHES, 2023)
The present research has endeavored to define the affecting relationship between direct marketing and purchasing behavior for the consumers of durable goods in Mosul because there are continuous communications among organizations, such as commercial agencies and a large number of parties, such as importers, distributors and consumers. These parties aim to get information from the organizations that produce durable goods and their policies and ways of consumers convincing and influencing him towards those durable goods. Despite the fact that there is a number of studies related to the knowledge of direct marketing and purchasing behavior, such studies has in fact ignored the deep affecting relationship between them As a result, the present research has investigated these two dimensions trying to find out the affecting relationship between them.